The Utilization and Impact of Dopamine Transporter Imaging in Diagnosing Movement Disorders at a Tertiary Care Hospital in Greece - Georgia Xiromerisiou; Iro Boura; Eleni Barmpounaki; Panagiotis Georgoulias; Efthimios Dardiotis; Cleanthe Spanaki; Varvara Valotassiou (Biomedicines)
Background/Objectives: The introduction of dopamine transporter scan (DaTscan) in clinical diagnostics has revolutionized the way clinicians approach movement disorders, offering valuable insights into presynaptic striatal dopaminergic deficits and revealing subjacent neurodegeneration. The aim of our study was to evaluate the impact of DaTscan on diagnostic decisions regarding movement disorders, particularly Parkinson’s disease (PD) and atypical parkinsonian syndromes, under real-world circumstances in Greece. Methods: We retrospectively analyzed data from 360 patients who underwent a DaTscan examination between 2018 and 2023 at a tertiary hospital in Greece, including referrals from both movement disorder specialists and general neurologists, either hospital-based or in private practice. Demographics, primary referral symptoms, and both pre-scan and post-scan diagnoses were collected and analyzed. Results: The mean age in our cohort was 60 ± 13.5 years, and tremor was the leading referral symptom (40.8%). The initial diagnosis changed in nearly half of the cases (48.3%) following DaTscan. Significant shifts included transitions from an “Unclear” or “Dystonia” diagnosis to “Parkinson’s disease” in 78.1% and 72.7% of patients, respectively. However, the particularly high concordance rates between pre-scan and post-scan diagnosis for “Vascular parkinsonism” (100%), “Parkinson’s disease” (89.3%), and “Essential/Dystonic Tremor” (86%) suggest that the test may have been over-utilized or ordered beyond its intended indications. Conclusions: DaTscan markedly enhances diagnostic accuracy for movement disorders, particularly for general neurologists, addressing the complexities of overlapping clinical presentations. Continuous medical training is essential to ensure the cost-effective utilization of DaTscan in routine clinical practice; ongoing technological advancements will further refine and expand their applications, benefiting both patients and the broader medical community.